Enhanced Hydrogel Materials: Incorporating Vitamin C and Plant Extracts for Biomedical Applications - Magdalena Kędzierska; Katarzyna Sala; Magdalena Bańkosz; Klaudyna Grzela; Piotr Potemski; Krzysztof Miernik; Bożena Tyliszczak (Molecules, 2024)
In recent years, the utilization of natural components has become crucial across various industries, including medicine. Particularly in biomedical contexts, hydrogel materials are of significant importance. Therefore, the objective of this research was to develop and analyze hydrogel materials infused with vitamin C. A key focus of this study was to conduct multiple syntheses with varying levels of vitamin C to explore the feasibility of creating materials with adjustable properties. The produced hydrogels underwent comprehensive physicochemical evaluation. The findings of this examination verified the correlation between the vitamin C content and the specific characteristics of the hydrogels. It was determined from these results that the samples displayed both sorptive and antioxidative capabilities, enabling their potential application in wound dressings or other biomedical uses. A notable benefit of these hydrogels is their adaptability, allowing for modifications to achieve desired attributes tailored to particular applications.